Silver nitrate functionalized rice husk-derived graphene oxide as a nanocarrier for pH-responsive drug delivery - Garwal, Kamal; Rawat, Kundan Singh; Arya, Tanuja; Sati, Satish; Tewari, Chetna; Pal, Mintu; Pande, Veena; Jung, Yong Chae; Sahoo, Nanda Gopal (SPRINGER, 2025)
In this study, graphene oxide (GO) derived from rice husk was functionalized with silver nitrate (AgNO3) through a chemical co-precipitation method, and its biomedical applications were systematically investigated. Drug release experiments revealed a pH-responsive profile, where at pH 4.0 the cumulative release reached 32.6 ± 1.6% after 24 h, compared to 12.4 ± 1.8% at pH 7.4, highlighting its potential for targeted delivery to cancer cells. Reactive oxygen species (ROS) analysis and flow cytometry demonstrated that RH-GO/AgNO3 treatment elevated oxidative stress and triggered apoptosis in HeLa cells. Furthermore, 5-fluorouracil (FU) was successfully loaded onto the nanocomposite surface via non-covalent interactions. Cytotoxicity assessment by MTT assay showed that FU-loaded RH-GO/AgNO3 had the strongest anticancer activity, with an IC50 value of 256.3 µg/mL. ROS levels in treated HeLacells increased significantly (40.17%) compared to the control group (19.45%), and flow cytometry confirmed a reduction in cell viability (69.5%) accompanied by enhanced apoptosis (early: 8.3%, late: 4.0%) and necrosis (18.2%). Collectively, these findings indicate that RH-GO/AgNO3-FU induces cancer cell death predominantly via apoptosis. Overall, this work demonstrates that agricultural waste-derived nanomaterials can serve as cost-effective and sustainable platforms for advanced drug delivery in cancer therapeutics.